Microbial landscape patients with advanced sterile pancreatic necrosis in the dynamics of complex treatment - V. P. Saganov; N. V. Fatkullin; S. B. Butukhanov; N. B. Gorbachev; D. I. Reshetnikov; V. P. Budasheev (Acta Biomedica Scientifica, 2015)
Method of gas chromatography - mass spectrometry was used for the study of microbial landscape of patients with pancreatonecrosis. It was found that the provision of sterile necrotic destruction dysbiosis occurs that requires correction during the treatment. Unlike conventional methods of diagnosis of infection pancreatogenic gas chromatography - mass spectrometry allows to express mode (3 hours) monitored landscape microbial degradation pancreatogenic patients. In patients with necrotizing pancreatitis concentration of organisms was determined in serum on admission, on day 5, day 10, day 15, day 20 of treatment. Data on the composition of microorganisms, participants of widespread sterile necrotic destruction when assessing the overall microecological status, obtained for each patient allow to get a qualitatively new comprehensive information to make adequate antibiotic therapy and complex treatment that significantly broadens the etiology of this disease.